If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 93 = 10m + 13 Reorder the terms: 93 = 13 + 10m Solving 93 = 13 + 10m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-10m' to each side of the equation. 93 + -10m = 13 + 10m + -10m Combine like terms: 10m + -10m = 0 93 + -10m = 13 + 0 93 + -10m = 13 Add '-93' to each side of the equation. 93 + -93 + -10m = 13 + -93 Combine like terms: 93 + -93 = 0 0 + -10m = 13 + -93 -10m = 13 + -93 Combine like terms: 13 + -93 = -80 -10m = -80 Divide each side by '-10'. m = 8 Simplifying m = 8
| -2(u-8)=4u+40 | | 8x-3=33-4x | | (x+3)(2x-4)=(x-2)(3x+1) | | 2.6y-1.6y-5.1=2.9 | | b^2-c^2= | | z^2+24z=0 | | 2y-5-3= | | r/4+28=0 | | 49a^2+100=0 | | ln(x)=0.1x-0.1 | | 9y-38=5(1[y-2]1) | | -(9x-3y+2)= | | 10x+8=2x+4 | | 6y+1=11 | | -2a+8=-7a-7 | | 2(1-8c)=8-3(6c+1)+4c | | 3.2x+5=11 | | 5e^1x=3e^1x | | 3x+2x=-15+5 | | 6z=17-29 | | 0.8(x+50)+0.4x=76 | | x^3+8x^2+4x+2=0 | | x+7=4x+9 | | 2x-17+63=180 | | x+3/x-2=3x+1/2x-4 | | 8m^2+20mn-18m-35n=0 | | x^4-11x^2-18x-8=0 | | 18-5+5h-11=9h+19-3h | | 10(x-8)=-114 | | 27=(5-u)3 | | -6=9-3p | | 8+2x-6=9x+9-6x |